Positive Politeness Strategies on Billboards for Legislative Candidates in Banyumas Regency in 2024 - Chusni Hadiati; Ely Triasih Rahayu; Sri Nani Hari Yanti; Kuntarto Kuntarto (Journal of Language and Literature, 2025)
This study examines positive politeness strategies in commissive speech acts on billboards of legislative candidates in the Banyumas Regency in 2024. Prospective legislative candidates use this billboard to capture votes in their constituencies. Campaign billboards often contain political promises as a form of commissive speech acts.  This study aims to fill the gap in previous research that has not examined commissive speech acts in the context of campaign billboards, emphasizing a pragmatic approach to understanding how language functions in political communication. All the data were in the form of text from 210 billboards photographed along Banyumas protocol roads, and 30 of them contained positive politeness. The data were analyzed based on positive politeness strategies according to Brown and Levinson’s theory. The results showed that legislative candidates used eight positive politeness strategies to express commissive speech acts. Those strategies are giving promises, giving reasons, being optimistic, being concerned about the hearer’s wants, making jokes, using group identity markers, giving gifts to the hearer, and using exaggeration. These strategies help convey campaign messages clearly and attract the attention of potential voters. This research contributes to understanding the use of language strategies in the context of political campaigns and proposes further research to evaluate the effectiveness of these strategies in winning voters’ votes. The findings are expected to provide practical benefits for legislative candidates and enrich the study of pragmatics in the political context.